2010
DOI: 10.1007/s00277-010-1070-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-inducible factors in mantle cell lymphoma: implication for an activated mTORC1→HIF-1α pathway

Abstract: Aberrant activation of phosphoinositide-3 kinase/Akt (PI3K/Akt) and mammalian target of rapamycin (mTOR) signaling is implicated in the pathogenesis of mantle cell lymphoma (MCL). We previously showed oncogenic activation of PI3K/Akt pathway in a subset of MCL patients. In this study, we investigated downstream the immunohistochemical expression of (Ser2448)pmTOR [indicative of mTOR complex 1 (mTORC1) activation status] as well as of hypoxia-inducible factor 1 alpha (HIF-1α), hypoxia-inducible factor 2 alpha (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
3
18
0
Order By: Relevance
“…Lymphomas were found to show hypoxic features, based on the expression of main endogenous hypoxic marker, HIF1a. Constitutive stabilization of HIF1a was found in the majority of patients with diffuse large B-cell lymphoma and follicular lymphoma (22), as well as in mantle cell lymphoma (18). Targeting hypoxia in solid tumors is one of the current approaches to prevent cancer angiogenesis, metastasis, and drug resistance, and it became also an emerging strategy in hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphomas were found to show hypoxic features, based on the expression of main endogenous hypoxic marker, HIF1a. Constitutive stabilization of HIF1a was found in the majority of patients with diffuse large B-cell lymphoma and follicular lymphoma (22), as well as in mantle cell lymphoma (18). Targeting hypoxia in solid tumors is one of the current approaches to prevent cancer angiogenesis, metastasis, and drug resistance, and it became also an emerging strategy in hematologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor hypoxia activates adaptive transcriptional programs, including HIF1a, that promote cell survival, motility, invasiveness, drug resistance, and neoangiogenesis in multiple myeloma (16,17), associated with more aggressive tumor (18). We have shown that hypoxia induces egress of multiple myeloma cells from the bone marrow to the circulation and facilitates their homing to the new bone marrow niches in myeloma.…”
Section: Introductionmentioning
confidence: 93%
“…Kueck showed that decreased glucose uptake by resveratrol in several cancer cell lines was mediated by downregulated pyruvate kinase M2 expression through inhibition of mTOR signaling (16). HIF-1a induction in malignant cells is closely linked to PI3K/Akt and mTOR signaling (27)(28)(29), which are frequently involved in cancer cell proliferation, metabolism, and survival (30). In breast cancer cells, estrogen-induced HIF-1a accumulation was shown to occur through the PI3K/Akt pathway leading to mTOR phosphorylation (31).…”
Section: Discussionmentioning
confidence: 99%
“…PI3K/AKT/mTOR signaling plays a central role in the development of both solid and hematological cancers [50]. Several lines of evidence indicate that aberrant activation of this pathway is common in both Hodgkin's lymphoma (HL) and various NHL subtypes, including FL, MCL and DLBCL [51][52][53][54][55][56][57][58][59][60][61][62][63][64]. The malignant lymphoproliferative effect of increased PI3K activity was demonstrated in transgenic mice expressing an activated PI3K, resulting in an infiltrative lymphoproliferative disorder similar to that observed by loss of the tumor suppressor PTEN [65].…”
Section: Bcr Signaling In Normal B Cellsmentioning
confidence: 99%